"Climatic-affective atmospheres": A conceptual tool for affective scholarship in a changing climate. (November 2019) - Verlie, Blanche
Abstract: This paper engages with the concept of affective atmospheres which has gained prominence in affect studies and suggests that in this era of global climate change, we need to 'acclimatise' this term. Working with a range of empirical examples, I argue that we can understand the climatic and affective to be entangled processes that co-produce each other. Working with the conceptual affordances of affective atmospheres offers much potential for research investigating the emotional and affective dimensions of climate change, enabling considerations that go beyond the individualism and anthropocentrism of more conventional approaches. Additionally, attuning to the climatic dimensions of affective atmospheres lessens the representational baggage of this term by moving beyond a metaphorical use of 'atmosphere'. The refined concept I propose, climatic-affective atmospheres, offers promising opportunities for contributing to more effective and ethical social responses to climate change, for example, by enabling attention to how climate change reconfigures, disrupts, shapes and directs humans, and how everyday human affective practices contribute to changing or stabilising climate. Highlights: Climatic-affective atmospheres 'acclimatises' affective atmospheres. Offers opportunities for research into climate change mitigation and adaptation. Affords consideration of planetary and epochal affective forces. Emphasizes the entanglement of affect and climate.